Structural Behavior of Recycled Aggregate Concrete Beam-Column Connection in Presence of Micro Concrete at Joint Region. (August 2017) - Marthong, C.; Sangma, A.S.; Choudhury, S.A.; Pyrbot, R.N.; Tron, S.L.; Mawroh, L.; Bharti, G.S.
Abstract: This paper investigates the effect of addition of micro concrete on the behavior of RC exterior beam-column connections prepared with recycled coarse aggregate (RCA) under the reversed cyclic loading. The results on mechanical strength evaluation of concrete showed an optimum replacement of 30% of natural coarse aggregate (NCA) by RCA. To extend the application of RCA concrete to structural elements, four beam-column specimens with two each of 30% RCA and 100% RCA were cast and the joint region of one specimen of 30% RCA and 100% RCA were cast with a micro concrete. A reference specimen was also prepared using 100% NCA and then subjected to a similar cyclic load. It was observed that, RCA specimens resulted in a brittle mode of failure as compared to NCA specimen. However, the presence of a micro concrete improved the damage tolerance, load resisting capacity and hence the seismic parameters such as stiffness degradation, ductility and energy dissipation increased. Further, the addition of micro concrete in RCA specimens presented a lower damage indices and higher principal tensile stresses, which are comparable to the NCA specimen. Conclusively, strengthening of joint region using micro concrete is found to have a significant contribution in improving the seismic performance of RCA beam-column connections.